Gestational trophoblastic disease: a profile of 37 cases - Shrivastava, Sushruta; Gandhewar, Manisha R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to study the demographic details, pattern of presentation and response to the treatment in the patients presenting with Gestational Trophoblastic Disease (GTD). Methods: The present study was conducted in a tertiary teaching institute as a retrospective plus prospective study over a period of 5 years from August 2004 to August 2009. Total 37 cases were studied out of which 16 were studied retrospectively from the case record and 21 were studied prospectively. Patients were evaluated on the basis of their age, number of deliveries, history of abortion or molar pregnancy and the treatment received. Results: 37 cases of gestational trophoblastic disease were studied in a period of 5 years from August 2004 to August 2009. The incidence of gestational trophoblastic disease was 1in 600 deliveries with the mean age of patients being 26.9 years. Most common chief complaint at presentation was bleeding per vaginum after a period of amenorrhoea seen in 31 patients (84%) followed by hyperemesis seen in 8 (19%) patients. Out of 37 patients 29 (78%) had complete mole & 8 (22%) had partial mole, the ratio of being 3.6:1. Complete cure rate in present study was seen in 31 out of 37 (84%) patients and mortality was seen in 2.7%. Conclusions: Gestational trophoblastic disease is seen most commonly in reproductive age group. This is a highly curable tumor even in the presence of distant metastasis.